The Influence of Knowledge of Mother Who Have Baby 6-12 Months on Supplementary Feeding - Suryani, Elvi; Harahap, Maryam Latifah; Rangkuti, Nur Aliyah; Batubara, Novita Sari; Siregar, Rya Anastasya; Siregar, Ratna Dewi (PT Inovasi Pratama Internasional, 2022)
Based on data from the Health Organization (WHO) in 2002 reported that 54% of deaths were caused directly or indirectly by undernutrition and malnutrition. IV pijorkoling, southeast Padangsidimpuan sub-district in 2022. This type of research is descriptive using a total sampling of 30 respondents. Collecting data using a questionnaire sheet, researched based on influence, age, education, occupation, parity and sources of information. The majority of respondents with less influence are 18 people (60%), the majority are less than 20-40 years old as many as 16 people (53.34%), the majority have less influence have a high school education as many as 15 people (50%), the majority have less influence are household workers as many as 14 people, (46.67%), the majority of respondents with low influence received information from health workers as many as 18 people (60%) and the majority with less influence based on parity of mothers who gave birth 3-4 times as many as 10 people (33.33%). The majority of the influence of mothers who have babies 6-12 months regarding complementary feeding is still lacking, so it is hoped that mothers will increase their influence and increase awareness and follow the instructions of health workers.